Real-time tracking system for a moored oil tanker: A Kalman filter approach - Paulo Malheiros (2013)
This paper presents a tracking system developed to study the behavior of an oil tanker moored at the Berth â â Aâ â of the LeixÃµes Oil Terminal, Porto, Portugal. A brief description of the local environmental conditions and the existing operational conditions at that oil terminal are presented. Due to extreme outdoor working conditions a Kalman filter was implemented to ensure the robustness and reliability of the obtained measurements. Tests were performed in laboratory on a physical model of a moored oil tanker at a scale 1/100. The results were compared with a commercial motion capture system installed in laboratory. The presented measurement system was developed as part of the DOLPHIN project that aims to study the behavior of moored ships in harbors. Â© Springer International Publishing Switzerland 2013.